2020
DOI: 10.33003/fjs-2020-0403-296
|View full text |Cite
|
Sign up to set email alerts
|

Production of Laccase by Fungi Isolated From Soil via Submerged Fermentation Using Corn Cob as Substrate

Abstract: One of the limitations of large scale application of laccase (EC 1.10.3.2) is the inability to produce them in large quantity at an affordable cost. This study was carried out to screen indigenous fungi for their ability to produce laccase using the locally available substrate. Five soil samples were collected and diluted serially, 0.1 mL of the 10-5 and 10-6 dilutions were inoculated onto Potato dextrose agar (PDA) plates. The fungal isolates were identified based on their macroscopic and microscopic characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In their species, T. atroviride and T. harzianum were recorded as the most vital laccase producers compared with other Trichoderma species [16,57]. Singh et al [58] and Nuhu et al [59] revealed that laccase production from Trichoderma sp. was affected highly by the incubation period and the temperature and found that incubation for 6-9 days at 25-30 °C was convenient for laccase production by Trichoderma species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their species, T. atroviride and T. harzianum were recorded as the most vital laccase producers compared with other Trichoderma species [16,57]. Singh et al [58] and Nuhu et al [59] revealed that laccase production from Trichoderma sp. was affected highly by the incubation period and the temperature and found that incubation for 6-9 days at 25-30 °C was convenient for laccase production by Trichoderma species.…”
Section: Discussionmentioning
confidence: 99%
“…It was stated that laccase production from Trichoderma sp. was obtained with high concentrations after 6-9 days of incubation at 25-30 °C Singh et al [58] and Nuhu et al [59]. Also, nitrogen sources play an essential role in microbial cell walls, proteins involving enzymes, amino acids, peptides, and nucleotide synthesis [70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation